1994
DOI: 10.1093/treephys/14.7-8-9.997
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration of beech stands and transpiration of beech leaves subject to atmospheric CO2 enrichment

Abstract: Beech trees (Fagus sylvatica L.) show reduced stomatal conductance and increased leaf area index in response to increased atmospheric CO(2) concentration. To determine whether the reduction in stomatal conductance results in lower stand evapotranspiration, we compared transpiration on a leaf-area basis and stand evapotranspiration on a ground-area basis in young European beech trees growing in greenhouses at ambient (360 +/- 34 micro mol mol(-1)) and elevated (698 +/- 10 micro mol mol(-1)) CO(2) concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…From a substantial number of recent studies examining leaves from forest trees, no evidence was found of stomatal adjustment in response to elevated CO 2 (Ellsworth et al 1995;Teskey 1995;Körner & Würth 1996;Tognetti et al 1996). These findings contrast with those reported for the dense sapling stands of Beech of Overdieck & Forstreuter (1994) which describe a significant reduction in the evapotranspiration rate under elevated CO 2 , despite of a 45% increase in LAI and a comparatively small decrease (18%) in stomatal conductance, perhaps this is attributable to the very special behaviour of small saplings not transferable to bigger trees (Loehle 1995). Grassland ecosystems, however, generally tend to reduce their water consumption under elevated CO 2 (Owensby et al 1997;Zaller & Arnone 1997;Jackson et al 1998).…”
Section: Evapotranspirationmentioning
confidence: 76%
“…From a substantial number of recent studies examining leaves from forest trees, no evidence was found of stomatal adjustment in response to elevated CO 2 (Ellsworth et al 1995;Teskey 1995;Körner & Würth 1996;Tognetti et al 1996). These findings contrast with those reported for the dense sapling stands of Beech of Overdieck & Forstreuter (1994) which describe a significant reduction in the evapotranspiration rate under elevated CO 2 , despite of a 45% increase in LAI and a comparatively small decrease (18%) in stomatal conductance, perhaps this is attributable to the very special behaviour of small saplings not transferable to bigger trees (Loehle 1995). Grassland ecosystems, however, generally tend to reduce their water consumption under elevated CO 2 (Owensby et al 1997;Zaller & Arnone 1997;Jackson et al 1998).…”
Section: Evapotranspirationmentioning
confidence: 76%
“…This was primarily a result of our incorporating Chen et al, 1997aChen et al, , 1997bEwers et al, 1999;Lawson et al, 2001;Lee et al, 1997;Mayeux et al, 1997;Mullholland et al, 1997Mullholland et al, , 1998Rowland-Bamford et al, 1991;Rudorff et al, 1996;Sims et al, 1999woody 8 Ceulemans et al, 1995Idso et al, 1993;Jach et al, 2000;Overdieck and Forstreuter, 1994;Tingey et al, 1996 global field data, which meant that LAI data were aggregated from experimental plots having soils of differing texture, composition and nutrient composition. Fertilization regimes also differed between studies; nitrogen (N) was added alone or with small amounts of phosphorus (P) and potassium (K), equal parts N:P:K, or large amounts of macronutrients (N, P, K) with small additions of micronutrients (i.e., S, Zn).…”
Section: Standardization Of Datamentioning
confidence: 99%
“…The daily pattern of E per unit of leaf area was also not affected in a different experiment on F. sylvatica using the branch-bag technique (Dufre# ne et al, 1993). However, evapotranspiration on a ground-area basis was reduced and leaf-area index increased in a small stand of F. sylvatica grown in elevated [CO # ] (Overdieck & Forstreuter, 1994).…”
Section: mentioning
confidence: 99%